Gender Equality in Context : Policies and Practices in Switzerland. - Liebig, Brigitte (Ebscodelete 2020-10-19., 2016)
Gender Equality has not yet been achieved in many western countries. Switzerland in particular has been a latecomer in integrating women in politics and economy. Taking Switzerland as a case study, the authors critically reflect the state of gender equality in different policy areas such as education, family and labor. The collection of articles reveals how gender policies and cultural contexts interact with social practices of gender (in)equality. They also outline the gender(ed) effects of recent changes and reform strategies for scientists, politicians and practitioners.